2016
DOI: 10.1167/iovs.15-17877
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Fusional Vergence Ranges and Heterophoria in Infants and Preschool Children

Abstract: PurposeBinocular alignment typically includes motor fusion compensating for heterophoria. This study evaluated heterophoria and then accommodation and vergence responses during measurement of fusional ranges in infants and preschoolers.MethodsPurkinje image eye tracking and eccentric photorefraction (MCS PowerRefractor) were used to record the eye alignment and accommodation of uncorrected infants (n = 17; 3–5 months old), preschoolers (n = 19; 2.5–5 years), and naïve functionally emmetropic adults (n = 14; 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…In the current study there was a higher percentage of children (3/13) than adults (1/11) who could not fuse through BI prism. This is reasonable in that preschoolers have demonstrated a mean divergence fusional range of close to 6pd at a similar viewing distance of 80 cm (Sreenivasan et al, 2016 ). For some young children, who didn't fuse initially, ramping from 4 pd to 6 pd did help them maintain fusion.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In the current study there was a higher percentage of children (3/13) than adults (1/11) who could not fuse through BI prism. This is reasonable in that preschoolers have demonstrated a mean divergence fusional range of close to 6pd at a similar viewing distance of 80 cm (Sreenivasan et al, 2016 ). For some young children, who didn't fuse initially, ramping from 4 pd to 6 pd did help them maintain fusion.…”
Section: Discussionmentioning
confidence: 68%
“…At the moderate viewing distance (1 m), percentage of adaptation was higher in base-in than in base-out conditions for both age groups. This adaptation might be helpful in relieving stress on the divergence fusional vergence system, given that the divergence fusional vergence range was significantly smaller than the convergence range at a similar viewing distance (Sreenivasan et al, 2016 ). The mean percentage of BO adaptation in adults [48% (SD ± 0.26) – Figure 4 , Panel B] was consistent with values found in previous studies of adults (Henson & Dharamshi, 1982 ; McCormack, 1985 ; North & Henson, 1981 , 1982 ; North, Sethi, & Owen, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infants and small children are not able to follow instructions, and so data collected from them can reflect only reflex behavior. We recorded reflex alignment responses in the presence of prism driving convergence and divergence while uninstructed naive participants aged 3-5 months, 2.5-5 years, or 20-32 years viewed a naturalistic cartoon image subtending 6° vertically by 2.5° horizontally at an 80-cm viewing distance (Sreenivasan et al 2016). Recordings of realignment responses to prism indicated that, on average, the three naive groups had matched reflex fusional vergence ranges that compared well with adults from previous findings in the literature (Figure 3).…”
Section: Maintaining Alignment Of the Eyesmentioning
confidence: 99%